The entrepreneurship-motherhood nexus: A longitudinal investigation from a boundaryless career perspective. Issue 1 (9th February 2015) - Lewis, Kate V.; Harris, Candice; Morrison, Rachel; Ho, Marcus
Abstract : Purpose: – The purpose of this paper is to use boundaryless career theory as a perspective from which to explore understanding related to the interplay between life-stage and career transitions in women; and, specifically, the life-stage-related event of motherhood relative to the transition from corporate employment to self-employment. Design/methodology/approach: – A qualitative longitudinal research design was operationalized over a four-year period and data from both primary and secondary sources were collected in relation to four New Zealand case studies. Findings: – The findings highlight how life-stage events such as motherhood can have a profound influence on both the perception and enactment of careers and career transitions. In total, two primary micro-processes were identified in relation to the career transitions of the female participants into self-employment and were labeled "traditional employment" (relating to role change; integrating work and life domains; opportunity seeking; and support) and "creating boundaries" (relating to: compartmentalization of responsibility, life-stage events, work models, and business growth and success). Research limitations/implications: – Exploratory in nature; small in scale; limited to one geographic context. Originality/value: – The authors attempt to add a more nuanced understanding of the notion of boundaryless careers in relation to entrepreneurship generally and the transition of a group of women into self-employment specifically. Both the discourse and pragmatics of boundaries between work/life and past careers/new careers is more salient in terms of success than possibly historically understood in this domain, and the enactment of boundaries richer and more diverse than theory may currently account for.